Analisis Minat Siswa Terhadap Ekstrakurikuler Bola Voli di SMP Negeri 37 Semarang : Analisis Minat Siswa Terhadap Ekstrakurikuler Bola Voli di SMP Negeri 37 Semarang - Safitri, Mirna Sandra; Kusuma P, Bertika; Ratimiasih, Yulia; Suprapti, Suprapti (Universitas Hamzanwadi, 2024)
The purpose of this study was to examine how much interest students have in extracurricular volleyball, and to find out the factors that influence it. This research method is descriptive quantitative with a survey method and using a questionnaire or questionnaire. The subjects of this study were 7th and 8th grade students totaling 398 respondents. The instrument is a questionnaire, with validity testing through expert judgment, and analyzing data using quantitative descriptive statistics with %. The results showed that most students' interest was in the low category 64.57% or as many as 257 students, followed by the very low category 26.38% or 105 students, then the high category 9.05% or 36 students, and the very high category 0% or none. Factors that influence low student interest, namely, internal factors due to training schedules that do not match students' free time and lack of interest in extracurricular volleyball, followed by physical conditions that are less supportive, external factors, namely lack of support from parents or family and in a community environment where there is no routine volleyball training. So it is concluded that students' interest in extracurricular volleyball as a whole is in the low category.